Just in Tyneside English. Issue 4 (14th March 2021) - Woolford, Kaleigh
Abstract: The present study evaluates the ongoing development of just as a discourse marker in Tyneside English. To capture the diachronic development of just in real‐time, the study focuses on a sample of 34 adolescent speakers from the Diachronic Electronic Corpus of Tyneside English (Corrigan et al.). The results of an accountable analysis of the verb phrase (N = 4, 386) show that the depreciatory use of just is increasing across real time, while other uses remain stable. Further investigation reveals a significant association of depreciatory just with narrative discourse contexts. A recent framework of context‐modulated multifunctionality (Wiltschko et al.) has been used to postulate the functional development of just as a rhetorical story‐telling device. More broadly, this paper contributes to the growing body of discourse markers analyzed through the variationist lens, offering a systematic and replicable methodology that will enable robust comparative analyses of the feature's development across world Englishes.